SCHOOL MANAGEMENT TRAINING FOR SCHOOL PRINCIPLES IN WEST JAVA PROVINCIAL GOVERNMENT - Jakaria, Jakaria; Saripah, Iip; Kamil, Mustafa; Saepudin, Asep (Jurnal Empowerment, 2024)
Training is a systematic process of imparting knowledge, skills and behavior to individuals or groups in order to improve their abilities and productivity in work or daily life.Through training activities, employees have a great opportunity to absorb new values ​​that have not existed so far, so that with these new patterns they can improve their profession in carrying out the tasks assigned to them.This article was prepared by utilizing literature study as a writing method. In addition, the authors also confirm the information obtained with data from interviews. The research results show thatThe advantages of e-learning-based training such as those conducted by the West Java BPSDM are the flexibility of time and place for participants, more affordable costs, and the ability to reach participants from various regions or countries. However, the weakness of this training is the limited direct interaction, especially for participants who do not have the same access to technology and the internet.